Cardiac rhythm management devices and electroconvulsive therapy: a critical review apropos of a depressed patient with a pacemaker - Kokras, N; Politis, A. M.; Zervas, I.M.; Pappa, D.; Markatou, M.; Katirtzoglou, E.; Papadimitriou, G.N. (J ECT, 2011)
Electroconvulsive therapy (ECT) is an effective treatment and, with the proper risk-minimizing strategies, is relatively safe even in depressed patients with cardiovascular diseases. Specifically, patients with cardiac rhythm management devices (CRMDs) require particular attention because no controlled trials exist to support current empirical recommendations. We present a depressed patient with a pacemaker successfully treated with ECT, and we critically review the relevant literature. Pooled results from 63 patients and 821 ECT sessions showed that 90% of ECT sessions have been performed on depressed patients with their pacemakers in sensing mode and rate adaptation, where available, activated as well. Only 4% of sessions were performed with those functions disabled, whereas no data was available for 6% of ECT sessions. Pooled results from case series and reports highlight a discrepancy between current clinical practice and many guidelines. Electroconvulsive therapy is probably safe in depressed patients with asynchronous fixed-rate pacemakers, although there is a risk of ventricular tachycardia and fibrillation. A larger body of case series and reports suggests that there might be no need to convert synchronous demand pacemakers to asynchronous fixed-rate pacing. Regarding patients with implantable cardioverter defibrillators, antitachycardia treatment was deactivated during most ECT sessions. In depressed patients with CRMDs anticholinergics might be best avoided. In all cases, proper ECT procedures, namely, patient and pacemaker electrical isolation, strict grounding and adequate muscle relaxation along with interrogation and monitoring of CRMDs before and after each session should ensure uncomplicated electroconvulsive treatments.
Keywords: *Pacemaker, Artificial; Accidents; Adult; Antidepressive Agents/therapeutic use; Arrhythmias, Cardiac/*etiology/*prevention & control; Depressive Disorder, Major/*complications/*therapy; Drug Resistance; Electroconvulsive Therapy/*adverse effects; Emergency Medical Services; Equipment Design; Female; Guidelines as Topic; Humans; Male; Middle Aged; Risk Assessment; Suicide, Attempted; Tachycardia, Ventricular/epidemiology/etiology; Ventricular Fibrillation/epidemiology/etiology